Small energy spread electron beams from laser wakefield acceleration by self-evolved ionization injection. (24th January 2018) - Wang, Jinguang; Feng, Jie; Zhu, Changqing; Li, Yifei; He, Yuhang; Li, Dazhang; Tan, Junhao; Ma, Jinglong; Chen, Liming
Abstract: We experimentally demonstrate generation of quasi-mono-energetic electrons from pure nitrogen gas via ionization injection induced by self-evolved laser pulses. By means of self-focusing and self-compression, we are able to reduce the injection length to 200 μ m and obtain the acceleration distance over several Rayleigh lengths that leads to the generation of quasi-mono-energetic electron beams with peak energy of 185 MeV and energy spread of 6%. This uncomplicated and maneuverable method suggests that the interaction of femtosecond laser pulses with moderate energy ∼1 J with pure nitrogen gas is advantageous for achieving stable and small energy spread electron beam.